Verification Index for the Repositioning of a Single Implant Analog in the Correct Place: A Clinical Technical Case Report - Socratis Thomaidis (Reports, 2026)
Background and Clinical Significance: Implant impressions can present inaccuracies, affected by many factors, such as impression technique, impression material, and parallelism or lack thereof among the implants. The use of a verification index can assess the accuracy of the mastercast and can be used in order to adjust the inaccuracy of the mastercast. This article presents a technical variation in established verification-index procedures, followed by implant analog repositioning, which can be used in case of an impression inaccuracy; Case Presentation: A patient with a moderate gag reflex received an implant. The impression of an implant and a prepared tooth was made. At the metal try-in, an inaccuracy of the mastercast was found, attributed to the final impression. A technique was illustrated, describing a polymethyl methacrylate (PMMA) verification index fabrication, followed by implant analog repositioning in the removable die of the master cast with the use of acrylic resin. This method may be used as an alternative to repeating the impression in selected clinical situations, but it is time-consuming, technique-sensitive, and needs meticulous handling; Conclusions: This is a viable technique and may represent an alternative to repeating the impression in selected clinical situations. Therefore, the clinical workflow can be reduced by one appointment. It can be helpful for patients with a moderate to severe gag reflex, since it can minimize the discomfort and stress for the patient and the dentist.